Tacrolimus prevents von Willebrand factor secretion by allostimulated human glomerular endothelium. Issue 9 (11th June 2018) - Béland, S.; Désy, O.; Ung, R. V.; Vallin, P.; Latulippe, E.; Riopel, J.; De Serres, S. A.
Abstract : Little is known about the endothelial injury caused directly by circulating donor‐specific antibodies (DSAs) during antibody‐mediated rejection. von Willebrand factor (vWF) is a highly thrombotic glycoprotein stored in Weibel‐Palade bodies in endothelial cells. It has been shown that its secretion is triggered by allostimulation. Calcineurin‐like phosphatases regulate pathways involved in vWF secretion. Therefore, we hypothesized that tacrolimus would prevent alloantibody‐induced glomerular lesions, in part via inhibition of vWF secretion from endothelial cells. Here, we used a human in vitro model of glomerular endothelium expressing HLA class I and II antigens and demonstrated that anti–HLA class II antibodies elicit a higher endothelial release of vWF than do anti–HLA class I antibodies in cell supernatants. We observed that tacrolimus treatment decreased vWF secretion after stimulation with both classes of anti‐HLA antibodies and decreased platelet adhesion on allostimulated endothelial cells in a microfluidic chamber. In kidney recipients, tacrolimus trough levels were negatively associated with vWF blood levels. These results indicate that direct disruption of hemostasis via vWF secretion is a potential mechanism of antibody‐mediated injury in patients with DSAs. Our results further suggest that the targeting of microcirculation hemostasis may be beneficial to prevent the development of microangiopathic lesions in antibody‐mediated rejection. Abstract : The authors observe that tacrolimus reduced von Willebrand factor secretion from endothelial cells treated with anti‐HLA antibodies, and that in kidney recipients, tacrolimus trough levels correlated negatively with von Willebrand factor blood levels.